Aktivitas Antibakteri Loloh (Obat Tradisional Bali) Air Perasan dan Air Rebusan Daun Sirih terhadap Bakteri Streptococcus pyogenes Penyebab Radang Tenggorokan - I Made Sumarya; I Wayan Suarda; Ni Luh Gede Sudaryati (Jurnal Kimia Sains dan Aplikasi, 2019)
Sore throat is a respiratory infection caused by a bacterial infection of Streptococcus pyogenes. Betel leaf is used for loloh (traditional medicine) which has antimicrobial activity. The purpose of this study was to determine the content of active compounds and the antibacterial activity of the boiled water and juice of betel leaf against Streptococcus pyogenes. Explorative research using GC-MS method was used to identify and determine the abundance (content) of active compounds from loloh while the experimental research with the Randomized Post Test Only Control Group Design was carried out by treating the samples in four groups those are the negative control group with distilled water, the positive control group with 30 μg vancomycin, the treatment group with boiled water of betel leaf and betel leaf juice water to prove the antibacterial activity of loloh. The antibacterial activity data of the study results were analyzed statistically nonparametric through the Kruskal-Wallis test. The results showed that the betel leaf boiled water contained 0.472% hydroxicavicol active compound and had an average antibacterial activity of 6.50±0.224 mm against Streptococcus pyogenes bacteria. Whilst the juice of betel leaves did not contain active compounds and had no antibacterial activity.